Gastropod Community On Seagrass Ecosystem in Makalisung coast - Kaseger, Cindy; Lalita, Jans Djoike; Tilaar, Ferdinand Frans; Tombokan, John L.; Mandagi, Stephanus V.; Ngangi, Edwin L. A. (Sam Ratulangi University, 2021)
The aim of the research is to know various species of gastropods and gastropod community structure through species density, percent density, dominant species, and association of species of gastropods on seagrass ecosystem. Research with the method of quadrat transect is put perpendicular to the coastline. Gastropod species are found in the seagrass ecosystem on the Makalisung coast consist of 9 species, 7 families, and 4 ordos. Gastropod community structure on seagrass ecosystem is found with species density is highest Cymbiola nivosa as big as 0.64 (ind/m2) with highest percent density 34.04 %. Diversity of species of gastropods on four-station that H’> 1 highest in fouth station as big as H’= 1.72. The dominance of species is highest Cymbiola nivosa as big as C=0.44, where the result of research in generally dominancy C < 0.25 belong to low. Association of species of gastropods on seagrass ecosystem found three characteristics, (1) classifying of positive association is Cypraea tigris and Monetaria annulus, Cypraea tigris and Cymbiola nivosa, Strombus labiatus and Cyclope pellucida, Strombus labiatus and Cymbiola nivosa, Monetaria annulus and Cerithiun nodulosum, Cymbiola nivosa and Cerithiun nodulosum; Cerithiu nodulosum and Angaria dephinus and Faunus ater. (2) Classification of not associated Angaria dephinus and association close to zero (0,04) is Monetaria annulus and Cymbiola nivosa. (3) Classifying of negative association based on the result of the research shows most of the negative pairs of gastropod species on seagrass ecosystem.Keywords: Gastropod; Density; Diversity; Dominance; AssociationAbstrakTujuan penelitian ini adalah mengetahui jenis-jenis Gastropoda dan struktur komunitas Gastropoda melalui Kepadatan spesies (Ind/m2), Kepadatan relatif (%), Dominansi spesies (C), dan asosiasi antarspesies Gastropoda pada ekosistem lamun. Penelitian dengan metode garis transek kuadrat yang ditempatkan tegaklurus garis pantai. Spesis gastropoda yang ditemukan di ekosism lamun pantai Makalisung, terdiri atas 9 spesies , 7 famili, dan 4 ordo. Struktur komunitas gastropoda di ekosistem lamun ditemukan dengan kepadatan total spesis tertinggi pada Cymbiola nivosa sebesar 0,64 (ind/m2) dengan kepadatan relatif tertinggi 34,04 %; keanekaragaman spesis gastropoda keempat stasiun H’> 1 di mana tertinggi stasiun 4 sebesar H’= 1,72; dominansi total tertinggi adalah spesis Cymbiola nivosa sebesar C=0,44, di mana hasil penelitian secara umum dominansi C < 0,25 adalah tergolong rendah. Asosiasi spesis gastropoda di ekosistem lamun ditemukan tiga ciri, (1) klasifikasi golongan asosiasi positif adalahCypraea tigris dan Monetaria annulus,Cypraea tigris dan Cymbiola nivosa, Strombus labiatus dan Cyclope pellucida, Strombus labiatus dan Cymbiola nivosa, Monetaria annulus dan Cerithiun nodulosum, Cymbiola nivosa dan Cerithiun nodulosum; Cerithiu nodulosum dan Angaria dephinus dan Faunus ater. Klasifikasi golongan tidak berasosiasi (2) Angaria dephinus dan asosiasi mendekati zero (0,04) yaitu Monetaria annulus dan Cymbiola nivosa. Dan klasifikasi golongan asosiasi negatif, hasil penelitian sebagian besar menunjukkan asosiasi negatif pasangan spesis gastropoda di ekosistem lamun.Kata kunci : Gastropoda, Kepadatan, Diversitas, Dominansi, Asosiasi.